Free space measurement technique on dielectric properties of agricultural residues at microwave frequencies - Wee, Fwen Hoon; Soh, Ping Jack; Mohd Suhaizal, Abu Hassan; Nornikman, Hassan; Mohd Ezanuddin, Abdul Aziz (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/